Photosystem I Is an Early Target of Photoinhibition in Barley Illuminated at Chilling Temperatures - Erling Tjus, Staffan (American Society of Plant Physiologists, 1998)
Light-induced damage to photosystem I (PSI) was studied during low-light illumination of barley (Hordeum vulgare L.) at chilling temperatures. A 4-h illumination period induced a significant inactivation of PSI electron transport activity. Flash-induced P700 absorption decay measurements revealed progressive damage to (a) the iron-sulfur clusters F(A) and F(B), (b) the iron-sulfur clusters F(A), F(B), and F(X), and (c) the phylloquinone A(1) and the chlorophyll A(0) or P700 of the PSI electron acceptor chain. Light-induced PSI damage was also evidenced by partial degradation of the PSI-A and PSI-B proteins and was correlated with the appearance of smaller proteins. Aggravated photodamage was observed upon illumination of barley leaves infiltrated with KCN, which inhibits Cu,Zn-superoxide dismutase and ascorbate peroxidase. This indicates that the photodamage of PSI in barley observed during low-light illumination at chilling temperatures arises because the defense against active oxygen species by active oxygen-scavenging enzymes is insufficient at these specific conditions. The data obtained demonstrate that photoinhibition of PSI at chilling temperatures is an important phenomenon in a cold-tolerant plant species.